USE OF OVAPRIM WITH DIFFERENT DOSES ON SPERM QUALITY AND SPAWNING OF SIGNAL BARB (Labeobarbus festivus, Heckel 1843) - Rozi Ramadhani Putra; Netti Aryani; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on April until June 2015, at Hatchery and Breeding Laboratory of Fisheries and Marine Science Faculty, University of Riau. The aim of the research was to determine the effect of ovaprim with different doses on sperm quality of signal barb (L. festivus, Heckel 1843) and for completion of this research then the best dosage obtained through observations on sperm quality will then be injected against gonads mature male brood and then spawned with the female injected with the best dose (0.7 ml/kg body weight). The results showed that ovaprim on doses 0.7 ml/kg body weight gives the best results for the cement volume (0,013 ml/g), concentration (878 x 107), motility (79,46%), viability (84,07 %). results for spawning resulted in average: fertility rate (40,39 %), hatching rate (14,85 %), and survival rate within 5 days (38,07 %). Keywords : Ovaprim, Sperm Quality, Egg Hatching, Signal barb (Labeobarbus festivus, Heckel 1843).